PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN IPO DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Janiman, Janiman; Sahrian, Rian (LITERATUS, 2024)
Increasing competition in the business world has made companies actively expand their businesses; these activities certainly cannot be separated from capital, one of the ways for companies to obtain funds is by conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange. An interesting phenomenon when conducting an IPO is the phenomenon of underpricing. Underpricing is a phenomenon where the price of shares traded in the primary market is lower than the price of shares when traded in the secondary market. The purpose of this study was to determine the effect of return on equity, debt to equity ratio and company size on underpricing in companies conducting an IPO on the Indonesia Stock Exchange in 2016-2018. This type of research is basic research. The research method used is the verification method. The sampling technique uses a purposive sampling method that is based on certain criteria so that the number of samples obtained is 72 companies. The data analysis technique used is multiple regression analysis (partial test), which is processed using SPSS version 25.0 for windows. Based on the results of the study, return on equity affects underpricing, firm size influences underpricing, while the debt to equity ratio has no effect on underpricing.